2019
DOI: 10.1186/s12913-019-3989-1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review and narrative synthesis on the risks of medical discharge letters for patients’ safety

Abstract: Background: Healthcare systems worldwide have adopted the electronic medical record (EMR). EMRs are an efficient method of interprofessional communication, and can improve data availability for secondary research purposes. The discharge summary (DS) is a crucial document for both interprofessional communication, and coding of data for research purposes. We aimed to assess the completeness of our EMRs by assessing the presence of a DS in the EMR. Additionally, we evaluated the presence of indicators for a missi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 59 publications
2
58
0
Order By: Relevance
“…Medical discharge summaries, or discharge letters, are a key communication tool for patient safety [1]. Australian national indicators for quality use of medicines in hospitals state that all discharge summaries should include "a current, accurate and comprehensive list of medicines" and "medication therapy changes and explanations for changes" [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical discharge summaries, or discharge letters, are a key communication tool for patient safety [1]. Australian national indicators for quality use of medicines in hospitals state that all discharge summaries should include "a current, accurate and comprehensive list of medicines" and "medication therapy changes and explanations for changes" [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognised, in Australia and internationally, that discharge summaries prepared by hospital physicians (including medical interns, junior medical officers and senior medical staff) often include incomplete or incorrect medication information [1,3,4]. Medication lists may be inaccurate, and medication changes made in hospital are often not documented, or they may be documented but not explained [3,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,[13][14][15][16][17][18] However, in practice the delivery of discharge instructions often remains rushed and essential details for facilitating continuity of care such as diagnosis, medication, lifestyle and follow-up information are not always exchanged. [13,[19][20][21][22][23][24] Despite the growing body of literature on quality of discharge communication and its impact on HCP and patient-related outcomes in HICs, similar evidence from low and middleincome countries (LMICs) remains relatively scarce. [25] Some single-site observational studies have evaluated discharge practices and found issues regarding deficient documentation, guidelines, standardised procedures and patient education.…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of patient complaints and litigation originate from poor communication 4. Correspondence that is delayed, not patient centred, and lacking information has been highlighted as a risk to patient safety 5. Writing prompt letters directly to patients can help reduce these risks 6…”
mentioning
confidence: 99%